Interaction Between Arousals and Ventilation During Cheyne-Stokes Respiration in Heart Failure Patients: Insights From Breath-by-Breath Analysis - Pinna, Gian Domenico; Robbi, Elena; Bruschi, Claudio; La Rovere, Maria Teresa; Maestri, Roberto (Frontiers in Medicine, 2021)
Study Objectives. Arousals from sleep during the hyperpneic phases of Cheyne-Stokes respiration with central sleep apnea (CSR-CSA) in patients with heart failure are thought to cause ventilatory overshoot and a consequent longer apnea, thereby sustaining and exacerbating ventilatory instability. However, data supporting this model are lacking. We investigated the relationship between arousals, hyperpnea and post-hyperpnea apnea length during CSR-CSA. Methods. Breath-by-breath changes in ventilation associated with the occurrence of arousal were evaluated in 18 heart failure patients with CSR-CSA, apnea-hypopnea index ≥15/h and central apnea index ≥5/h. The change in apnea length associated with the presence of arousal during the previous hyperpnea was also evaluated. Potential confounding variables (chemical drive, sleep stage) were controlled for. Results. Arousals were associated with a large increase in ventilation at the beginning of the hyperpnea (+76±35%, p<0.0001), that rapidly declined during its crescendo phase. Around peak hyperpnea, the change in ventilation was -8±26% (p=0.14). The presence of arousal during the hyperpnea was associated with a median increase in the length of the subsequent apnea of +4.6% (Q1, Q2: -0.7%, 20.5%; range: -8.5%, 36.2%) (p=0.021). The incidence of arousals occurring at the beginning of hyperpnea and mean ventilation in the region around its peak were independent predictors of the change in apnea length (p=0.004 and p=0.015, respectively; R2= 0.78.). Conclusions. Arousals from sleep during CSR-CSA in heart failure patients are associated with a rapidly decreasing ventilatory overshoot at the beginning of the hyperpnea, followed by a tendency towards a slight ventilatory undershoot around its peak. On average, arousals are also associated with a modest increase in post-hyperpnea apnea length; however, large increases in apnea length (>20%) occur in about a quarter of the patients.